DEVELOPING DYNAMIC STRESS TEST FOR BANKING SYSTEM WITH ADAPTIVE LEARNING AGENTS: AN AGENT BASED APPROACH - Raissa Raswan, Tara
Nowadays, world economic development cannot be parted from the financial system because financial growth closely linked to economic growth. The system which is comprises of all parties that involved in money flow, i.e. financial markets, instruments, and institution. A financial system which categorized as a sophisticated one is involving a higher degree of intermediation with a higher degree of dependency, hence it possesses a higher risk of failure. The importance of managing financial system stability mainly caused by the high cost of financial system failure. Based on several studies, the financial system failure is one of the costliest failure compared to other.